The Influence of External Cooling Load on the Distribution of Temperature and Humidity in Conditioned Spaces - Karudin, Arwizet; Sharma, Jai Kumar; Leni, Desmarita; Abbas, Muhammad Rabiu; Adriansyah, Adriansyah (Universitas Negeri Padang, 2024)
Air conditioning is not only important for the comfort of occupants in a building but also for various industrial processes. In the air conditioning process, a device called an Air Conditioner (AC) is required. The AC load can originate from inside the room and from outside the room. This study aims to determine the influence of increased cooling load from outside the room on the distribution of temperature and air humidity inside the conditioned room. The method used in this study involved conditioning four rooms. Two rooms of almost the same size were equipped with two AC units each, while the other two rooms used one AC unit each. Temperature and air humidity data inside the rooms were recorded every 20 minutes, as well as the outside air temperature. Dry bulb thermometer (Tdb) and wet bulb thermometer (Twb) were used to record temperature and humidity data, along with an environmeter. The research data were processed using available equations and with the assistance of a psychrometric chart. The research findings revealed that the average distribution of temperature and air humidity in the meeting room and office headroom of the Pertamina DP-LPG Office in Binjai was 20°C-23°C and 59%-65%. For the distribution office and sales service room of the Pertamina Fuel Filling Terminal in Kisaran, the distribution of temperature and air humidity was 25°C-29°C and 62%-66%. From the test results, it can be concluded that the distribution of temperature and air humidity is highly influenced by the capacity of the AC units and the cooling load entering the room.